PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK AUDIO VISUAL BAGI PEMBELAJARAN EKONOMI MATERI KURS VALUTA ASING DI SMA NEGERI 8 MALANG - Zulfa Fatati Nadya Nafis; Sapir * (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2016)
This research is done with the objective to develop Audio Visual Comics instructional media which can be used in Economics learning in senior high school with foreign currency exchage rate subject. Research and development model used in this reaearch is Borg & Gall model with 3 kinds of validity tests. Those tests are subject test, media test, and product trial test. Product trial test consist of small group test and field test. The collecting of the validity data is using questionnaire and written test instrument. Based on the result of the research can be concluded that Audio Visual Comics has judged very appropriate to be used in economics learning either in subject aspect, media aspect and its effectivity in classroom.Keywords: foreign exchange rate, audio-visual comic, instructional media